Factors Influencing Access to Sexual and Reproductive Health Information among Adolescents Aged 12-19 Years in Mukono Municipality Schools: A Cross-Sectional Study - Josephine Namyalo; Dissan Sentumbwe; Annet Patience Nakalega; Jacqueline Kobusingye; Emmanuel Otieno (Journal of Community Health Research)
Background: Adolescent sexual and reproductive health is one of the essential health care services that promote a adolescent’s health. Complications of unwanted pregnancies lead to school dropouts’, disability and mortality.  However, many adolescents 12-19 years face barriers to reproductive health information about their health and rights. And are unable to access services needed to protect their health. This study aimed to assess factors influencing access to Sexual and Reproductive Health Information among adolescents aged 12-19 years in Mukono municipality schools, Uganda. Methods: Analytical cross-sectional survey and simple random sampling were used to select 384 participants between July and December 2022 in Mukono municipality. A Self-administered structured was used to collect data. Data was analyzed using descriptive statistics, chi-square test, and a modified Poisson regression model. Results: Findings showed the mean age of participants was 16.1 (S.D + 2) years. The proportion of access to information was 80.27%. Significant factors strongly associated with access to sexual and reproductive health information were being Moslem (OR: 0.284 (0.089-0.912)], going to hospital [OR: 2.350 (1.143-4.828)], distance 3-5 Kms from home to nearest health facility [OR: 0.41 (0.176-0.912)]. Conclusion: Two of every ten participants had access to Sexual Reproductive Health and Rights information. Significant determinants were radio media and print newspapers. Stakeholders should advocate for adolescents’ increased access to healthcare information to avert the upsurge in related diseases. Policy makers should review and monitor new guidelines for Adolescent and School health inclusive of sexuality and reproductive health. Thus, improve health equity for all.